Fully-graded low-carbon concrete and preparation method thereof
Through full-grade design and the introduction of stone powder and ultrafine powder, the concrete ratio is optimized, and the problem of performance degradation in the existing low-carbon concrete technology is solved, efficient low-carbon and environmentally friendly concrete is achieved, and the mechanics of concrete is improved. Performance and durability.
Patent Information
- Application Number
- CN202411300017.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-01-10
AI Technical Summary
When the existing low-carbon concrete technology reduces the amount of cement, it often decreases the mechanical properties and durability of concrete, and the particle shape and grading of the machine sand are difficult to control, resulting in poor concrete working performance and mechanical properties, and existing solutions High cost or difficult to promote.
Using a full-grade matching design method, the concrete mix is optimized by introducing stone powder and ultrafine powder, combined with the modified Anderson model (MAAM), the ratio of gelled material and aggregate is adjusted to ensure that the particle accumulation curve is close to the target curve, and heavy calcium is used. As ultrafine powder, powder or fly ash mineral powder is used as ultrafine powder, and the distribution coefficient q is adjusted to meet different design needs and improve the compactness and working nature of concrete.
Without reducing the concrete performance, the amount of cement is significantly reduced, the mechanical properties and durability of concrete are improved, and carbon emissions are reduced, which is in line with the development trend of low-carbon and environmental protection.
Smart Images

Figure CN119285278A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete, and in particular relates to a low-carbon concrete with a full-graded design and a preparation method thereof. Background Art
[0002] With the rapid development of economy, the demand for infrastructure construction in my country is growing. As one of the most widely used building materials, the high carbon emissions in the production process of concrete has become a major challenge to environmental sustainability. In particular, the production of cement, the key component of concrete, accounts for 12% of the country's total CO2 emissions (including process emissions) in the cement industry. Therefore, the development of low-carbon concrete is not only a need for environmental protection, but also a necessary measure to cope with global climate change.
[0003] The main technical routes of low-carbon concrete mainly include reducing cement dosage, optimizing concrete formula design, using machine-made sand and recycled aggregate, etc., but on the one hand, low cement dosage is often accompanied by a decrease in the mechanical properties and durability of concrete. On the other hand, although machine-made sand has its environmental advantages, its particle shape and gradation are difficult to control, which will cause poor working performance and mechanical properties of concrete. Chinese patent publication number CN117024074A discloses a low-carbon concrete containing a composite admixture. Although the cement dosage is low, the composite admixture is composed of 5-10% dopamine, 1-3% resorcinol, 1-3% small molecule alcohol amine compound, 0.5-1.5% amino silicone oil, and 0.1-0.5% hexadecyl trimethyl ammonium hydroxide. The composition is complex and the cost is high. Chinese patent publication number CN118181515A discloses a method for preparing low-carbon concrete, which introduces nano-scale SiO2 and a corresponding release device, greatly reducing the amount of cement, but also correspondingly increasing the cost and execution difficulty, and is not easy to promote on a large scale. Chinese patent publication number CN116535168A discloses a low-carbon concrete containing modified optical fiber particles and a preparation method thereof, which has the advantages of high early and long-term strength and good durability, but the acquisition of modified optical fiber particles will generate new environmental problems and higher energy consumption. Summary of the invention
[0004] The present invention provides a low-carbon concrete with a full-gradation design and a preparation method thereof to solve the problems existing in the prior art. The low-carbon concrete is fully graded from cementitious materials to aggregates, stone powder and ultrafine powder are introduced to improve the gradation, the proportion of concrete is systematically optimized, the amount of cement is reduced, and the performance of concrete is guaranteed while the concrete performance is guaranteed.
[0005] The present invention is implemented as follows: a low-carbon concrete with a full-grade design is composed of the following raw materials in parts by weight: 150-200 parts of cement, 40-80 parts of fly ash, 40-80 parts of mineral powder, 40-80 parts of stone powder, 40-80 parts of ultrafine powder, 700-900 parts of machine-made sand, 800-1000 parts of crushed stone, 140-200 parts of water, and 3-8 parts of water reducing agent; the proportion of cementitious material and aggregate is adjusted according to the modified Andreasen and Andersen model (MAAM) so that the stacking curve is as close to the target curve as possible. MAAM is shown in formula (1):
[0006]
[0007] In the formula, P(D i ) is less than D i The cumulative fraction of particles, in %, D i is the particle size of the particle, in μm; D max is the maximum particle size of the particles, in μm; D min is the minimum particle size of the particles, in μm; q is the distribution coefficient.
[0008] In the above technical solution, preferably, the ultrafine powder is heavy calcium powder or fly ash ore powder ultrafine composite powder, and the D50 of the ultrafine powder is less than 6 μm, and the D90 is less than 20 μm.
[0009] In the above technical solution, preferably, the MB value of the machine-made sand is not greater than 1.4.
[0010] In the above technical solution, preferably, the crushed stones are composed of small stones and medium stones, and the ratio of small stones to medium stones is 25%-50%:50%-75%.
[0011] In the above technical solution, preferably, the distribution coefficient q has a value of 0.23 to 0.30.
[0012] A method for preparing low-carbon concrete with full-grade design comprises the following steps:
[0013] 1) Determine the mix ratio of concrete according to the gradation design results;
[0014] 2) Mix the weighed machine-made sand and crushed stone and stir evenly, add cement, fly ash, mineral powder, stone powder and ultrafine powder, stir thoroughly until uniform, and obtain a mixture;
[0015] 3) adding the water reducer into the water and mixing evenly, and adding the water reducer into the mixture obtained in step 2) and stirring;
[0016] 4) After the mixing is completed, the concrete is poured into a mold and cured, and the low-carbon concrete is obtained after the curing is completed.
[0017] Traditional gradation design mainly focuses on the particle size distribution of aggregates. The mix design based on MAAM in this invention takes into account the overall stacking of cementitious materials and aggregates, which can effectively improve the compactness and workability of concrete, thereby enhancing the mechanical properties and durability of concrete. In addition, by adjusting the q value to meet the needs of different concrete designs, this dynamic adjustment can better adapt to the changes in the ratio of coarse and fine particles in concrete to achieve the best stacking effect.
[0018] According to the closest packing theory, concrete often lacks ultrafine powders with smaller particle sizes than conventional cementitious materials such as cement and mineral powder, which limits the compactness and mechanical properties of concrete structures to a certain extent. Ultrafine powders can fill the tiny gaps between particles of cement, fly ash, mineral powder, etc., can reduce the amount of concrete water to a certain extent, and provide more contact surfaces for chemical reactions, which significantly improves the performance of concrete, thereby reducing the amount of cement without sacrificing the performance of concrete. The present invention creatively introduces ultrafine composite powders of heavy calcium powder or fly ash mineral powder as ultrafine powders. Compared with silica fume, they have a wider source and lower cost.
[0019] The advantages and positive effects of the present invention are:
[0020] Full gradation design optimization: The present invention optimizes the system from cementitious materials to aggregates based on MAAM, improves the gradation by introducing stone powder and ultrafine powder, ensures that the component particles in the concrete can be close to the closest packing, and improves the mechanical properties and durability of the concrete.
[0021] Low-carbon and environmentally friendly: The present invention helps to reduce carbon emissions in the concrete production process by systematically optimizing the mix ratio and reducing cement usage, which is in line with the development trend of low-carbon and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a concrete gradation diagram of Example 1 of the present invention;
[0023] Figure 2 This is a concrete gradation diagram of Example 2 of the present invention;
[0024] Figure 3 This is a concrete gradation diagram of Example 3 of the present invention;
[0025] Figure 4 This is a concrete gradation diagram of Example 4 of the present invention;
[0026] Figure 5 This is a concrete gradation diagram of Example 5 of the present invention;
[0027] Figure 6 This is the concrete gradation diagram of Example 6 of the present invention. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0029] Embodiment 1:
[0030] According to MAAM, the concrete mix ratio was optimized based on the particle size distribution of each raw material (q = 0.28), and the raw material components were obtained: 150 parts of cement, 40 parts of fly ash, 60 parts of mineral powder, 80 parts of stone powder, 60 parts of heavy calcium powder, 900 parts of machine-made sand, 1000 parts of crushed stone, 175 parts of water, 5 parts of water reducer, and the particle size distribution was as follows: Figure 1 shown.
[0031] The preparation method of low-carbon concrete is as follows: weigh according to the ratio, mix the machine-made sand and crushed stone and stir evenly, add cement, fly ash, mineral powder, stone powder and heavy calcium powder, stir thoroughly until uniform, and obtain a mixture; add the water reducer into the water and mix evenly, and add it to the mixture and stir; after stirring, pour the concrete into a mold for curing.
[0032] Embodiment 2:
[0033] According to MAAM, the concrete mix ratio was optimized based on the particle size distribution of each raw material (q = 0.28), and the raw material components were obtained: 200 parts of cement, 40 parts of fly ash, 80 parts of mineral powder, 40 parts of stone powder, 40 parts of heavy calcium powder, 700 parts of machine-made sand, 1000 parts of crushed stone, 200 parts of water, 3 parts of water reducer, and the particle size distribution was as follows: Figure 2 shown.
[0034] The preparation method of low carbon concrete is the same as that in Example 1.
[0035] Embodiment 3:
[0036] According to MAAM, the concrete mix ratio was optimized based on the particle size distribution of each raw material (q = 0.24), and the raw material components were obtained: 160 parts of cement, 80 parts of fly ash, 40 parts of mineral powder, 40 parts of stone powder, 80 parts of heavy calcium powder, 800 parts of machine-made sand, 800 parts of crushed stone, 140 parts of water, 8 parts of water reducer, and the particle size distribution was as follows: Figure 3 shown.
[0037] The preparation method of low carbon concrete is the same as that in Example 1.
[0038] Embodiment 4:
[0039] According to MAAM, the concrete mix ratio was optimized based on the particle size distribution of each raw material (q = 0.28), and the raw material components were obtained: 150 parts of cement, 40 parts of fly ash, 60 parts of mineral powder, 80 parts of stone powder, 60 parts of fly ash mineral powder ultrafine composite powder, 900 parts of machine-made sand, 1000 parts of crushed stone, 175 parts of water, 5 parts of water reducer, and the particle size distribution was as follows: Figure 4 shown.
[0040] The preparation method of low-carbon concrete is as follows: weigh according to the ratio, mix the machine-made sand and crushed stone and stir evenly, add cement, fly ash, mineral powder, stone powder and fly ash mineral powder ultrafine composite powder, stir until uniform, and obtain a mixture; add the water reducer into the water, mix evenly, and add it to the mixture and stir; after stirring, pour the concrete into a mold for curing.
[0041] Embodiment 5:
[0042] According to MAAM, the concrete mix ratio was optimized based on the particle size distribution of each raw material (q = 0.28), and the raw material components were obtained: 200 parts of cement, 40 parts of fly ash, 80 parts of mineral powder, 40 parts of stone powder, 40 parts of fly ash mineral powder ultrafine composite powder, 700 parts of machine-made sand, 1000 parts of crushed stone, 200 parts of water, 3 parts of water reducer, and the particle size distribution was as follows: Figure 5 shown.
[0043] The preparation method of low carbon concrete is the same as that of Example 4.
[0044] Embodiment 6:
[0045] According to MAAM, the concrete mix ratio was optimized based on the particle size distribution of each raw material (q = 0.24), and the raw material components were obtained: 160 parts of cement, 80 parts of fly ash, 40 parts of mineral powder, 40 parts of stone powder, 80 parts of fly ash mineral powder ultrafine composite powder, 800 parts of machine-made sand, 800 parts of crushed stone, 140 parts of water, 8 parts of water reducer, and the particle size distribution was as follows: Figure 6 shown.
[0046] The preparation method of low carbon concrete is the same as that of Example 4.
[0047] Comparative Example 1
[0048] The difference between this comparative example and Example 1 and Example 4 is that the particle size distribution is not designed for closest packing according to MAAM, the types and proportions of cementitious materials in the concrete components are different, and the others are the same.
[0049] Specifically, the raw material components are: 230 parts of cement, 80 parts of fly ash, 80 parts of mineral powder, 900 parts of machine-made sand, 1000 parts of crushed stone, 175 parts of water, and 5 parts of water reducing agent.
[0050] The preparation method of concrete is as follows: weigh according to the ratio, mix the machine-made sand and crushed stone and stir evenly, add cement, fly ash and mineral powder, stir thoroughly until uniform, and obtain a mixture; add the water reducer into the water, mix evenly, and add the water reducer into the mixture and stir; after stirring, pour the concrete into a mold for curing.
[0051] Comparative Example 2
[0052] The difference between this comparative example and Example 2 and Example 5 is that the particle size distribution is not designed for closest packing according to MAAM, the types and proportions of cementitious materials in the concrete components are different, and the others are the same.
[0053] Specifically, the raw material components are: 240 parts of cement, 80 parts of fly ash, 80 parts of mineral powder, 700 parts of machine-made sand, 1000 parts of crushed stone, 200 parts of water, and 3 parts of water reducing agent.
[0054] The preparation method of concrete is the same as that of Comparative Example 1.
[0055] Comparative Example 3
[0056] The difference between this comparative example and Example 3 and Example 6 is that the particle size distribution is not designed for closest packing according to MAAM, the types and proportions of cementitious materials in the concrete components are different, and the others are the same.
[0057] Specifically, the raw material components are: 220 parts of cement, 90 parts of fly ash, 90 parts of mineral powder, 800 parts of machine-made sand, 800 parts of crushed stone, 140 parts of water, and 8 parts of water reducing agent.
[0058] The preparation method of concrete is the same as that of Comparative Example 1.
[0059] Referring to GB / T 50081-2019 "Standard for Test Methods for Physical and Mechanical Properties of Concrete" and GB / T 50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", the compressive strength and durability of the concrete of Examples 1-6 and Comparative Examples 1-3 were measured, and the results are shown in Table 1.
[0060] Table 1 Concrete performance data
[0061]
[0062] As can be seen from Table 1 above, compared with the concrete of the prior art (Comparative Examples 1-3) provided by the present invention, the low-carbon concrete with full gradation design has higher compressive strength at 7 days and 28 days, and lower chloride ion diffusion coefficient at 28 days, which indicates that the present invention can improve the mechanical properties and durability of concrete. In addition, the low-carbon concrete of the present invention uses less cement without reducing the performance, and the cement usage is reduced by 16.7% to 34.8% compared with the comparative example, which helps to reduce carbon emissions and promote the development of a low-carbon economy.
[0063] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents, and these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A low-carbon concrete with full-grade design, characterized in that: The invention is composed of the following raw materials in parts by weight: 150-200 parts of cement, 40-80 parts of fly ash, 40-80 parts of mineral powder, 40-80 parts of stone powder, 40-80 parts of ultrafine powder, 700-900 parts of machine-made sand, 800-1000 parts of crushed stone, 140-200 parts of water, and 3-8 parts of water reducing agent; the proportion of cementitious material and aggregate is adjusted according to the modified Anderson model MAAM so that the stacking curve is as close to the target curve as possible. MAAM is shown in formula (1): In the formula, P(D i ) is less than D i The cumulative fraction of particles, in %, D i is the particle size, in μm; D max is the maximum particle size of the particles, in μm; D min is the minimum particle size of the particles, in μm; q is the distribution coefficient.
2. The fully graded low-carbon concrete according to claim 1, characterized in that: The ultrafine powder is a superfine composite powder of heavy calcium powder or fly ash ore powder, and the D50 of the ultrafine powder is less than 6 μm, and the D90 is less than 20 μm.
3. The fully graded low-carbon concrete according to claim 1, characterized in that: The MB value of the machine-made sand is not greater than 1.
4.
4. The fully graded low-carbon concrete according to claim 1, characterized in that: The crushed stones are composed of small stones and medium stones, and the ratio of small stones to medium stones is 25%-50%:50%-75%.
5. The fully graded low-carbon concrete according to claim 1, characterized in that: The distribution coefficient q is between 0.23 and 0.
30.
6. A method for preparing the fully graded low-carbon concrete according to claim 1, characterized in that: The steps include: 1) Determine the mix ratio of concrete according to the gradation design results; 2) Mix the weighed machine-made sand and crushed stone and stir evenly, add cement, fly ash, mineral powder, stone powder and ultrafine powder, stir thoroughly until uniform, and obtain a mixture; 3) adding the water reducer into the water and mixing evenly, and adding the water reducer into the mixture obtained in step 2) and stirring; 4) After the mixing is completed, the concrete is poured into a mold and cured, and the low-carbon concrete is obtained after the curing is completed.
Citation Information
Patent Citations
Low-carbon concrete and preparation method thereof
CN116535168A
Low-carbon concrete and preparation method thereof
CN117024074A
Preparation method of low-carbon concrete
CN118181515A